Challenges and Opportunities of Vermicompost Production for Sustainable Soil Health and Reduced Chemical Fertilizer Dependency: Evidence from Northern and Southern Bangladesh - Haque, Abdul; Miajy, Abdullah; Debnath, Manik; Sharif, Ahmed; Bhandari, Humnath (International Rice Research Institute, 2025)
"This study examines household-level vermicompost production and use in Northern and Southern regions of Bangladesh and evaluates its potential to improve soil health and reduce dependence on chemical fertilizers. A household survey was conducted among 200 vermicompost-producing households (100 per region) engaged in mixed farming systems. Data were collected using a structured questionnaire administered through a computerassisted personal interview platform. All surveyed households had received formal training on vermicompost production and were actively producing compost using locally available materials. Cow dung was the dominant raw material used by all households, while the use of crop residues and kitchen waste remained limited. Significant regional variation was observed in production intensity and output. Households in the Northern region used a higher number of composting carriers, completed more production cycles annually, and required less time per cycle, resulting in substantially higher annual compost production (557 kg per household/year) compared with the Southern region (110 kg per household/year). Vermicompost was primarily used for on-farm application, particularly during the Kharif-II and Rabi seasons. A large majority of households reported improvements in soil fertility and crop yields following vermicompost application. Reductions in chemical fertilizer use were widely reported, especially in the Southern region. Although only a small proportion of households sold vermicompost, income from sales was higher in the Northern region due to greater volumes and higher market prices. Despite these benefits, households faced production challenges, including worm mortality, moisture management difficulties, and limited access to raw materials and financial support. Nevertheless, most households expressed strong intentions to continue or expand vermicompost production. The findings indicate that vermicomposting represents a viable pathway for sustainable soil fertility management and livelihood improvement, provided that targeted technical, financial, and market support mechanisms are strengthened."